Experimental Latin American Cinema: History and Aesthetics - Depetris Chauvin, Irene (Imagofagia, 2021)
Sobre Cynthia Tompkins. Experimental Latin American Cinema: History and Aesthetics. Austin: University of Texas Press, 2013, 294 pp., ISBN 978-0292744158. Palabras clave: reseña, Cynthia Tompkins. Experimental Latin American Cinema: History and Aesthetics.